Distributional characteristics of VOT in children's voiceless aspirated stops and interpretation of developmental trends. - Koenig, Laura L. (Journal of Speech, Language & Hearing Research, 2001)
Numerous researchers have measured voice onset time (VOT) in children. Authors attempting to trace developmental trends in consonant voicing have frequently framed their hypotheses in terms of how children's VOT means and/or standard deviations compare to adult norms. However, data from previous studies suggest that children's VOTs may not be normally distributed. Specifically, rightward skew is observed in the voiceless aspirated stops, such that mean values exceed the medians. The current work presents detailed distributional analyses of VOTs in /p, t/ from 7 five-year-old children and 14 adults. Distributional non-normality was common in both the adult and child data, as measured by Shapiro and Wilk's W statistic. The children showed an insignificant but consistent tendency towards higher values of skew than the adults and greater differences between VOT mean and median values. The results suggest that theories of VOT development should not be based solely on means and standard deviations, but need to address the distributional characteristics of the data more fully. Reprinted by permission of the publisher.